Analysis of Competitiveness and Government Policy on Rice, Corn and Soybean Farming - Bowo, Prasetyo Ari; Nurayati, Aisyah; M. Imleesh, Rabeea Muhammad (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
Rice, corn and soybean is the strategic commodities and the government always maintains their availability. Indonesia still imports rice, corn and soybean and implements the policy of tariffs, taxes and subsidies on rice, corn, soybean imports and farming inputs. Central Java is the main producer of rice, corn and soybean with the contibution of Gross Regional Domestic Product of the food crop sub-sector to the highest Provincial GRDP in Indonesian. This research examines the competitiveness and the government policy towards rice, corn and soybean farming in Central Java Province. It uses secondary data of Farming Economic Analysis from the relevant agencies and scientific publications on the international price of rice, corn and soybean that is analyzed using the quantitative descriptive method with analysis tool of Policy Analysis Matrix (PAM). The PAM result shows that the rice farming in Cilacap Regency and the corn farming in Grobogan Regency have competitive and comparative advantage. The soybean farming in Grobogan only has a comparative advantage. Overall the government policies are protective towards the rice farming in Cilacap, but not protective towards the corn and soybean farming in Grobogan. The sensitivity analysis shows that the advantages and competitiveness of the rice farming in Cilacap and the corn and soybean farming in Grobogan are sensitive towards the international price changes of commodities and fertilizers, the labor cost changes, the exchange rate fluctuations of Rupiah towards USD, and the import tariff changes of commodities.